2023
DOI: 10.3390/nu15143125
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Iron Deficiency/Iron-Deficiency Anemia in Women: An Asian Expert Consensus

Rishma Dhillon Pai,
Yap Seng Chong,
Lyra Ruth Clemente-Chua
et al.

Abstract: The lack of standardized clinical practice impeding the optimal management of iron deficiency (ID) and iron deficiency anemia (IDA) in women is a global concern, particularly in the Asia-Pacific region. The aim of this study was to determine best practices through a Delphi consensus process. In Round 1, panelists were asked to rate their level of agreement with 99 statements across four domains: identification, diagnosis and assessment, prevention, and treatment of ID/IDA in women. In Round 2, panelists reappr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…These findings suggest that women of reproductive age remain particularly vulnerable to anemia. The increased risk in women aged 40-49 may be attributed to menorrhagia common during the perimenopausal period, while the elevated risk in women aged ≥70 years could be related to the higher incidence of chronic diseases and inflammation accompanying aging (6,(8)(9)(10). Consistent with other research, our study confirmed regional variations in anemia prevalence.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that women of reproductive age remain particularly vulnerable to anemia. The increased risk in women aged 40-49 may be attributed to menorrhagia common during the perimenopausal period, while the elevated risk in women aged ≥70 years could be related to the higher incidence of chronic diseases and inflammation accompanying aging (6,(8)(9)(10). Consistent with other research, our study confirmed regional variations in anemia prevalence.…”
Section: Discussionsupporting
confidence: 91%
“…Delayed cord clamping until 1–3 minutes after birth is a simple, but effective intervention to reduce newborn anaemia by facilitating placental transfusion and iron-rich blood flow to the newborn [ 47 , 50 ], while routine iron supplementation is recommended for high-risk infants 6 to 12 months of age [ 51 ]. Moreover, preventive iron supplementation is recommended for all pregnant women, non-pregnant adult women, adolescent girls, and perimenopausal women with a high prevalence of anaemia [ 52 ]. A recent meta-analysis found that consuming condiments and seasonings fortified with iron plus other micronutrients may prevent anaemia in the general population [ 53 ].…”
Section: Discussionmentioning
confidence: 99%